Educator Professionalism in The Independent Curriculum Through Digital Literacy Training for Teachers - Meidawati Suswandari; Annisa Prima Exacta; Giyatmi Giyatmi (Universitas Lambung Mangkurat, 2024)
This training aims to train teachers in Sukoharjo Regency in the independent curriculum by applying digital literacy as professional educators. The training method involves socialization, training, mentoring, and evaluation stages. The success target in this training is 40%. The training results show that the training stages are carried out in four stages: providing material, implementing an application in digital literacy learning, assisting teachers in creating and operating digital literacy, and evaluating this training. This training was carried out on February 6, 2023, with the results showing that 49 teachers in Sukoharjo Regency stated that they were very satisfied with the delivery of material by the presenters, a total of 27 people (55.1%). The benefits of this digital literacy training were in the very useful category for 34 teachers or 69.4%. Furthermore, in the continuation of this training, it was categorized from the data above as follows: 12 teachers felt it was very actionable, 31 teachers felt it could be followed up, and six teachers felt it was quite actionable. The evaluation data above stated that there was success in implementing this training, which reached above 40%.